187k views
2 votes
What is the result when x^3+ 7x^2+ 9x - 8 is divided by x+ 2?

User AmirHJ
by
5.9k points

2 Answers

4 votes

Answer:

Explanation:

What is the result when x^3+ 7x^2+ 9x - 8 is divided by x+ 2?-example-1
User Bidoubiwa
by
5.7k points
6 votes

Answer:


(x^3+7x^2+9x-8)/(x+2)=x^2+5x-1+(-6)/(x+2)

So the quotient is
1x^2+5x+-1 and the remainder is
-6.

Explanation:

We could do this by synthetic division since the denominator is a linear factor in the form
x-c.

Since we are dividing by
x+2=x-(-2), this is our setup for the synthetic division:

-2 | 1 7 9 -8

| -2 -10 2

______________

1 5 -1 -6

So the quotient is
1x^2+5x+-1 and the remainder is
-6.

So
(x^3+7x^2+9x-8)/(x+2)=x^2+5x-1+(-6)/(x+2).

We can also do long division.

x^2+5x-1

____________________

x+2| x^3+7x^2+9x-8

-(x^3+2x^2)

-------------------

5x^2+9x-8

-( 5x^2+10x)

--------------------

-x-8

-(-x-2)

--------------

-6

So we see here we get the same quotient,
x^2+5x-1. and the same remainder,
-6.

Now let's check our result that:


(x^3+7x^2+9x-8)/(x+2)=x^2+5x-1+(-6)/(x+2).

So I'm going to rewrite the right hand side as a single fraction:


(x^3+7x^2+9x-8)/(x+2)=((x+2)(x^2+5x-1))/(x+2)+(-6)/(x+2).


(x^3+7x^2+9x-8)/(x+2)=((x+2)(x^2+5x-1)-6)/(x+2)

Now let's focus on multiplying
(x+2)(x^2+5x-1).

We are going to multiply the first term of the first ( ) to every term in the second ( ).

We are also going to multiply the second term of the first ( ) to every term in the second ( ).


x(x^2)=x^3


x(5x)=5x^2


x(-1)=-x


2(x^2)=2x^2


2(5x)=10x


2(-1)=-2

---------------------------Combine like terms:


x^3+(5x^2+2x^2)+(-x+10x)+-2


x^3+7x^2+9x-2

So let's go back where we were in our check of
(x^3+7x^2+9x-8)/(x+2)=x^2+5x-1+(-6)/(x+2):


(x^3+7x^2+9x-8)/(x+2)=((x+2)(x^2+5x-1)-6)/(x+2)


(x^3+7x^2+9x-8)/(x+2)=(x^3+7x^2+9x-2-6)/(x+2)


(x^3+7x^2+9x-8)/(x+2)=(x^3+7x^2+9x-8)/(x+2)

We have the exact same thing on both sides so we did good.

User Hassan Saeed
by
5.9k points